SPIRITUAL INTELLIGENCE AMONG SECONDARY SCHOOL STUDENTS OF KASHMIR VALLEY - Bhat, Dr. Mohammad Sayid (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The research has shown that the development of spiritual intelligence contributes to students' overall wellbeing and success in their academic pursuits. In this context, a study has been carried out on the spiritual intelligence of secondary school students of Kashmir Valley in which a comparison has been made between male and female, rural and urban, government and private secondary school students. 600 sample subjects were randomly selected from 30 government and private secondary schools in Kashmir Valley. The Social Intelligence Scale developed by K.S. Misra (2014) was administered to sample subjects for the data collection. For the analysis of data, percentage statistics and t-tests were employed. The study results show that female secondary school students possess significantly higher spiritual intelligence than male students. The study also shows that rural students have more spiritual intelligence than urban students. Further, the study concluded that Kashmir Valley government students possess significantly lower spiritual intelligence than private secondary school students.